Multidrug resistant enteric fever in South Asia: unmet medical needs and opportunities - Parry, C; Ribeiro, I; Walia, K; Rupali, P; Baker, S; Basnyat, B (BMJ, 2019)
Investments in newer diagnostics and antimicrobial treatments are critical to improve management of enteric fever in South Asia, say Christopher Parry and colleagues.